RHEOLOGICAL TRANSITIONS AND THE PROGRESS OF MELTING OF CRUSTAL ROCKS - Barboza S.A.; Bergantz G.W. (My University, 1998)
High-grade igneous and metamorphic systems which possess a variable percentage of melt, may undergo a transition between crystal-supported and fully fluid behavior. The melt-fraction interval over which this transition occurs is not well constrained. We have conducted six series of numerical simulations of crustal melting using melt-fraction intervals between 0.05 to 0.15 for this mechanical transition. The results of these simulations demonstrate the dependence of convection and progress of melting on the rheological transition between solid and melt. Convective heat flux varied by a factor of 8 over the duration of the simulations (160 yr) and the mass of melt produced varied by nearly a factor of 4. The onset of convection in simulations with the most gradual rheological transition was suppressed. Convective heat flux and progress of melting were more sensitive to the melt-fraction interval for the rheological transition than to the composition of a range of crustal protoliths. The rheological transition between solid and melt may be one of the dominant factors controlling the thermal evolution of high-grade crustal rocks.
Keywords: ANATEXIS; MIXING; MELTS; PHASE EQUILIBRIA; RHEOLOGY; UNDERPLATING